L’économie sociale et solidaire : une nouvelle économie morale pour la Tunisie ? - Ester Sigillò; Damiano De Facci (L’Année du Maghreb)
The protest movements of the winter of 2010-2011, which led to the fall of the Ben Ali regime, put forward a number of socio-economic demands around the issues of employment, development and justice. Grievances have been mostly expressed by young people of the so-called marginalized areas of the country and, in general, by those social groups that have been excluded from the economic and social development policies of the old regime. These demands have been progressively taken up by emerging associations that set up new ways of doing development, facing the incapacity of the state to meet the needs of the population. In this context, the social and solidarity economy (SSE) became both a socio-economic «alternative» to state’s development strategies and a legitimate model for the associative action. Starting from the case study of the Southern region of Medenine, our article aims to show how the model of the SSE, crafted by international actors and elaborated in the national arena, allows at the same time the deployment of new hegemonic dynamics and the creation of new networks aiming at legitimizing the inclusion strategies of previously excluded social groups.